Periodic solutions of systems of two linear first-order ordinary differential equations with degenerate asymmetric matrix with derivatives - Er’omenko, V. O. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish sufficient conditions for the existence of a periodic solution of a system of two linear firstorder ordinary differential equations with degenerate asymmetric matrix with derivatives in the case of an arbitrary periodic inhomogeneity.